Experimental and ReaxFF‐based molecular dynamics studies of the reaction of oxygen with DR‐2 as a low global warming potential working fluid. Issue 23 (24th August 2021) - Tao, Neng; Cheng, Yuan; Lu, Song; Xing, Haoran; Shahid, Muhammad Usman; Lo, Siuming; Zhang, Heping
Abstract: The cis‐1, 1, 1, 4, 4, 4‐hexafluoro‐2‐butene (DR‐2 or HFO‐1336mzz(Z)) is a novel environmentally friendly working fluid with appropriate physicochemical characteristics. The present work firstly investigated the decomposition mechanism and thermal stability of DR‐2 in a oxygen (O2 )‐containing atmosphere at high temperature experimentally. The oxidative degradation features of DR‐2 were explored at the temperature of 473–1073 K and the products were monitored by GC–MS and IC. The experimental and ReaxFF‐based molecular dynamics results demonstrated the promotion effects of O2 on the DR‐2 decomposition. The participation of O2 molecules was supposed to lower the initial thermal decomposition temperature by 240 K approximately and increase the number of products such as hydrogen fluoride (HF), but the enhancement effect was weakened by the increasing reaction temperature. The reasonable Arrhenius parameters were calculated from the first‐order kinetic analyses‐based reactive molecular dynamics (RMD) simulations. Combined with the density functional theory, the pathways of initial oxidation decomposition product firstly observed in the experiment and RMD simulations were proposed in this study. These results may pave the way for further study of DR‐2 as a working fluid with lower global warming potential. Abstract : The promoting effect of O2 molecules on DR‐2 was investigated experimentally and theoretically at high temperature in this study. HF was one of the main products of thermal decomposition of DR‐2 with O2, and the ReaxFF MD simulation were in good agreement with the experimental results. And the process of O2 molecule attacking DR‐2 to form the oxidation products was deduced in combination with the DFT method.